Investment strategies in the Brazilian industry of aluminum cans: an analysis in the context of real options games - Costa, Leticia de Almeida (2015)
Objective – The purpose of this article is to analyze the impact of preemption (first move advantage, with the consequent emergence of negative externalities to competitors) in situations that consider the optimal moment for investment, in the context of asymmetric oligopolies, and using the options games method.Design/methodology/approach – The developed model was applied to the Brazilian aluminum can industry, in which three firms made up an asymmetric oligopoly, allowing strategic interactions and their consequences on firms’ investment decisions to be analyzed.Findings – In situations of preemption, the results show the relevance of using a dynamic model, allowing us to observe the importance of obtaining a competitive advantage in cost, and showing that it is possible to obtain monopoly profits or take advantage of isolated expansion for a longer period. If this advantage is great, rivals’ threat of preemption can be considered irrelevant, and that the firm will invest in monopolistic time, ignoring the possibility of rivals’ entry.Practical implications – In a competitive environment, firms need to decide whether the best strategy is to invest earlier, acquiring a competitive advantage over their rivals, or to postpone their investments, to acquire more information and mitigate the eventual consequences of market uncertainties. This work shows how to do it.Originality/value – This is the first paper that, by applying real options games, studies the impact of preemption of investment in the oligopolistic asymmetric environment of the Brazilian industry of aluminum cans.